Uzbek Lexicon and its Division - Abdinazarovich, Bazarov Sherali (European Journal of Life Safety and Stability (2660-9630), 2021)
This article deals with the origin of Uzbek lexicon, including obsolete words, phrases, terms, figurative expressions and dialectal words.